A Study Of Transcultural Convergence: The Influence Of North Indian Traditions On Tamil Nadu - Balasubramani. S (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The impact of North Indian traditions on the history of Tamil Nadu is a complex and multifaceted phenomenon that has evolved over centuries. It can be observed in various aspects of Tamil Nadu's culture, society, religion, and politics. The impact of North Indian traditions on Tamil Nadu's religious landscape is significant. The introduction of Hinduism and its various sects, including Shaivism, Vaishnavism, and Shakta traditions, has been influenced by North Indian religious practices and philosophies. Various North Indian dynasties, including the Cholas, Pallavas, and Chalukyas, played significant roles in the history of Tamil Nadu. The interactions and conflicts with North Indian rulers influenced the politics, administration, and culture of Tamil Nadu. Trade and commerce between North India and Tamil Nadu have led to cultural exchanges, the movement of people, and the spread of ideas, further influencing the region's history.